EXTERNAL FACTORS MOTIVATING SUCCESSFUL WOMEN ENTREPRENEURS: A STUDY OF WOMEN ENTREPRENEURS COMMUNITY IN A RURAL AREA - Riesta Devi Kumalasari*, Kukuh Lukiyanto , Agung Purnomo (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Traditional or rural societies typically maintain the cultural assumption that female entrepreneurship is unusual or taboo. Despite this assumption, many women in rural areas are, in fact, successful entrepreneurs, and they even act as the backbone of their family. Accordingly, this study investigated this phenomenon occurring in a community of the Pagentan Village in the Singosari District, Malang Regency. The purpose of this study was to examine the external factors affecting women in rural areas that made them successful in developing their businesses and the conflicts that continue to challenge them. Moreover, this is a qualitative research employing a phenomenological approach. Last, the conclusion of this research indicates that external factors encouraging the success of rural women entrepreneurship includes family support, environmental support, and supervisory institutions. The findings of this study can be used as a reference for inspiration to increase the number of women entrepreneurs in Indonesia, especially in rural areas. In addition, it can also be used as a reference for motivation to encourage women in becoming entrepreneurs.